A Colorimetric Assay to Enable High‐Throughput Identification of Biofilm Exopolysaccharide‐Hydrolyzing Enzymes. Issue 47 (27th July 2020) - Wang, Shaochi; Breslawec, Alexandra P.; Li, Crystal; Poulin, Myles B.
Abstract: Glycosidase enzymes that hydrolyze the biofilm exopolysaccharide poly‐β‐(1→6)‐ N ‐acetylglucosamine (PNAG) are critical tools to study biofilm and potential therapeutic biofilm dispersal agents. Function‐driven metagenomic screening is a powerful approach for the discovery of new glycosidase but requires sensitive assays capable of distinguishing between the desired enzyme and functionally related enzymes. Herein, we report the synthesis of a colorimetric PNAG disaccharide analogue whose hydrolysis by PNAG glycosidases results in production of para ‐nitroaniline that can be continuously monitored at 410 nm. The assay is specific for enzymes capable of hydrolyzing PNAG and not related β‐hexosaminidase enzymes with alternative glycosidic linkage specificities. This analogue enabled development of a continuous colorimetric assay for detection of PNAG hydrolyzing enzyme activity in crude E. coli cell lysates and suggests that this disaccharide probe will be critical for establishing the functional screening of metagenomic DNA libraries. Abstract : A colorimetric PNAG analogue has been developed that enables selective detection of biofilm dispersing PNAG glycosidase enzyme activity. This analogue enabled development of a continuous assay to measure PNAG hydrolyzing enzyme activity in crude E. coli cell lysates that can be used for functional screening of metagenomic DNA libraries (see figure).